Hermann & Valentiny and Partners : Codes - Waechter-Böhm, Liesbeth (Birkhäuser, 2008)
For twenty-five years, Hubert Hermann and François Valentiny have maintained their offices in Vienna and Luxemburg. Their architecture offersan experience beyondthe parameters of the zeitgeist and makes a highly individual contribution to the current architectural discussion.